Internalisasi Nilai Pendidikan Akhlak dalam Surat Al-Hujurat Ayat 11-13 Menurut Tafsir fi Zilalil Qur'an - Saiful Anwar (JIE (Journal of Islamic Education), 2021)
This study examines the implementation of moral education in QS. Al-Hujurat verses 11-13 in Sayyid Qutb's Tafsir Fi Zilalil Quran. The purpose of this research is to describe the messages and values ​​of moral education as contained in the letter Al-Hujurat verses 11-13. The benefits of this research are theoretically expected to provide a small contribution of thought or input that is useful for Islamic education, while practically this research is expected to provide a little contribution of thought, especially for researchers and readers in general in understanding the contents of the content or values ​​in the letter. Al-Hujurat verses 11-13. The data collection method in this thesis research is a qualitative method through searching data or library research, library data collection methods, reading and processing research materials. The source of the commentary book Fi Zhilalil Qur'an is supported by secondary sources which are related to the problem. Based on the results of research and data analysis, it can be concluded that: The values ​​of moral education contained in the Al-Hujurat verse 11-13 in the interpretation of Fi Zhilalil qur'an, namely the prohibition of making fun of, criticizing, calling badly, haram and prejudice , backbiting, finding fault with others and equality and ta'aruf. The study found that there are three types of interpretation used by sayyid qutub. The methods used are takhalli, tahalli and tajalli.